Green organic synthesis of N-methylpyrrolidine - Hoa, Nguyen Van; Tuan, Nguyen Anh; Thao, Phan Thanh; Huyen, Trinh Thi Thanh (Vietnam Journal of Science and Technology, 2016)
N-methylpyrrolidine was successfully synthesized in an aqueous medium by using methylamine and 1,4-dibromobutane in the presence of catalyst K2CO3 at a moderated temperature. Here, N-methylpyrrolidine was firstly synthesized via the green chemistry process, in which both the water solvent and potassium carbonate catalyst were inexpensive and environmentally friendly. Also, the reaction temperature was quite moderated at 900C. As a result, the current synthesis process was highly potential to implement in practice. Since the product yield directly depended on the operating conditions, the catalysts, temperature, ratio of reactants and solvent would be critical factors. In the present study, the structure of N-methylpyrrolidine product was confirmed by using the IR, 1H-NMR, 13C-NMR and Gas Chromatography-Mass spectroscopy (GC-MS).